Mutations conferring resistance to phenamil and amiloride, inhibitors of sodium-driven motility of Vibrio parahaemolyticus - Jaques, Sandford (The National Academy of Sciences, 1999)
The bacterial flagellum is powered by a rotary motor capable of turning the helical flagellar propeller at very high speeds. Energy to drive rotation is derived from the transmembrane electrochemical potential of specific ions. Ions passing through a channel component are thought to generate the force to power rotation. Two kinds of motors, dependent on different coupling ions, have been described: proton-driven and sodium-driven motors. There are four known genes encoding components of the sodium-powered polar flagellar motor in Vibrio parahaemolyticus. Two, which are characterized here, are homologous to genes encoding constituents of the proton-type motor (motA and motB), and two encode components unique to the sodium-type motor (motX and motY). The sodium-channel-blocking drugs phenamil and amiloride inhibit rotation of the polar flagellum and therefore can be used to probe the architecture of the motor. Mutants were isolated that could swim in the presence of phenamil or amiloride. The majority of the mutations conferring phenamil-resistant motility alter nucleotides in the motA or motB genes. The resultant amino acid changes localize to the cytoplasmic face of the torque generator and permit identification of potential sodium-interaction sites. Mutations that confer motility in the presence of amiloride do not alter any known component of the sodium-type flagellar motor. Thus, evidence supports the existence of more than one class of sodium-interaction site at which inhibitors can interfere with sodium-driven motility.